PERANCANGAN TANGAN PROSTHESIS BAWAH SIKU BERBASIS FLEXY HAND 2 DAN FLEX SENSOR - Firdhaus Hari Saputro Al Haris (Jurnal Teknoinfo, 2021)
One of the best ways to rehabilitate persons with disabilities is to use prostheses. However, not all persons with disabilities, especially those with disabilities on the hands can use all types of prosthesis hands. The purpose of this research is to develop Flexy Hand 2 into a 3D Printing-based prosthesis hand that is wider in its scope of use. The method used in this research is trial and error. The scope of the user of this prosthesis hand is a person with disabilities below the elbow who still has one other hand that still has at least 3 fingers. The result of this research is a prosthetic hand that can move the entire finger and can mimic it basic hand movements such as grasping objects and picking up objects with a delay between the transmitter and receiver modules ranging from 132 milliseconds to 260 milliseconds. The entire modules works at a voltage of 5V which means the hand can be turned using a portable power supply. Keyword: Disabilities, Prosthetic Hand, Flexy Hand 2, Flex Sensor, Trial and Error.